Enhancing students' understanding through mathematics projects - a mathematics teacher's experience - Dzuratul Ain binte Cik Mit, * (Sunway University College, 2010)
With an increasing need to broaden and expand the students? understanding in mathematics in the classroom, the creation of a variety of teaching and learning tools and strategies are of utmost importance. Using the appropriate teaching and learning form, opportunities can be provided for students to develop necessary skills and demonstrate their understanding in relevant areas. For the two mathematics courses in the CIMP curriculum, namely Mathematics of Data Management and Advanced Functions, mathematics projects are part of the teaching and learning activities that provide the opportunities for students to fulfill the expectations of the course and at the same time, enhance their degree of understanding of the concepts and ideas introduced. In this paper, the author will highlight the mathematics projects devised for both courses and share the experience and feedback from students on what had been implemented and learnt throughout the semester. Also, the hands-on experience with concepts and ideas, the skills developed and achievements made, as well as the constraints and challenges confronted will be discussed in the paper.